Adaptation of the Golgi Apparatus in Cancer Cell Invasion and Metastasis - Bui, Sarah; Mejia, Isabel; Díaz, Begoña; Wang, Yanzhuang (Frontiers in Cell and Developmental Biology, 2021)
The Golgi apparatus plays a central role in normal cell physiology by promoting cell survival, facilitating proliferation, and enabling cell-cell communication and migration. These roles are partially mediated by well-known Golgi functions, including post-translational modifications, lipid biosynthesis, intracellular trafficking, and protein secretion. In addition, accumulating evidence indicates that the Golgi plays a critical role in sensing and integrating external and internal cues to promote cellular homeostasis. Indeed, the unique structure of the mammalian Golgi can be fine-tuned to adapt different Golgi functions to specific cellular needs. This is particularly relevant in the context of cancer, where unrestrained proliferation and aberrant survival and migration increase the demands in Golgi functions, as well as the need for Golgi-dependent sensing and adaptation to intrinsic and extrinsic stressors. Here, we review and discuss current understanding of how the structure and function of the Golgi apparatus is influenced by oncogenic transformation, and how this adaptation may facilitate cancer cell invasion and metastasis.